2004
DOI: 10.1038/ni1123
|View full text |Cite
|
Sign up to set email alerts
|

Function of the drosophila pattern-recognition receptor PGRP-SD in the detection of Gram-positive bacteria

Abstract: The activation of an immune response requires recognition of microorganisms by host receptors. In drosophila, detection of Gram-positive bacteria is mediated by cooperation between the peptidoglycan-recognition protein-SA (PGRP-SA) and Gram-negative binding protein 1 (GNBP1) proteins. Here we show that some Gram-positive bacterial species activate an immune response in a PGRP-SA- and GNBP1-independent manner, indicating that alternative receptors exist. Consistent with this, we noted that PGRP-SD mutants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
194
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(198 citation statements)
references
References 34 publications
1
194
2
1
Order By: Relevance
“…Three Drosophila PGRPs -PGRP-SA, PGRP-SD, and PGRP-SC1 -recognize bacterial peptidoglycan and activate proteases that cleave Spaetzle, an extracellular cytokine-like protein present in insect hemolymph, which in turn serves as an endogenous activator of Toll [8,23,24] (Figure 4a). Activation of Toll initiates a signal The PGRP domain has three ␣ helices (red), five ␤ strands (yellow) and coils (cyan); the three disulfide bonds are in purple; MurNAc-pentapeptide is drawn in stick representation, with carbon, nitrogen, and oxygen atoms in green, blue, and red, respectively.…”
Section: Insect Pgrpsmentioning
confidence: 99%
“…Three Drosophila PGRPs -PGRP-SA, PGRP-SD, and PGRP-SC1 -recognize bacterial peptidoglycan and activate proteases that cleave Spaetzle, an extracellular cytokine-like protein present in insect hemolymph, which in turn serves as an endogenous activator of Toll [8,23,24] (Figure 4a). Activation of Toll initiates a signal The PGRP domain has three ␣ helices (red), five ␤ strands (yellow) and coils (cyan); the three disulfide bonds are in purple; MurNAc-pentapeptide is drawn in stick representation, with carbon, nitrogen, and oxygen atoms in green, blue, and red, respectively.…”
Section: Insect Pgrpsmentioning
confidence: 99%
“…PGRP-LC, PGRP-LE double mutants show a more dramatic phenotype to Bacillus and Gram Ϫ bacterial infection than either mutation alone, suggesting that PGRP-LE acts with PGRP-LC in the recognition of Gram Ϫ DAP-type peptidoglycan for the activation of the Imd pathway (24). PGRP-SD may be playing a similar role with PGRP-SA for activation of the Gram ϩ ͞Toll pathway (23).…”
mentioning
confidence: 99%
“…Gram ϩ PGN and Gram Ϫ PGN differ in the stem peptide portion; typical Gram ϩ bacteria have a lysine as the third amino acid, whereas Gram Ϫ bacteria and the Gram ϩ Bacillus have a diaminopimelic acid (DAP) in that position (22). Two other noncatalytic PGRPs, PGRP-LE and PGRP-SD, also play a role in activation of the Imd and Toll pathways, respectively (23,24). PGRP-LC, PGRP-LE double mutants show a more dramatic phenotype to Bacillus and Gram Ϫ bacterial infection than either mutation alone, suggesting that PGRP-LE acts with PGRP-LC in the recognition of Gram Ϫ DAP-type peptidoglycan for the activation of the Imd pathway (24).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that several PGRPs bind directly to PG, each with distinct preferences for binding Lys-type PGN or DAP-type PGN (16)(17)(18). Elegant genetic studies recently carried out in Drosophila revealed that D. melanogaster PGRP-SA (Dm-PGRP-SA) and -SD activate the Toll pathway (19,20), while Dm-PGRP-LC and Dm-PGRP-LE serve as receptors for the Imd pathway (21)(22)(23)(24). The immune phenotype of a loss-of-function mutant of Dm-Gram-negative bacteria binding protein1 (Dm-GNBP1) was indistinguishable from that of Dm-PGRP-SA, demonstrating that the two proteins are required to activate the Toll pathway in response to Gram-positive bacterial infection (25,26).…”
Section: How Is Lys-type Pg Recognized In Drosophila?mentioning
confidence: 99%